Effects of buffer layer and thermal annealing on the performance of hybrid Cu2S/PVK electrically bistable devices. (September 2016) - Li, Xu; Lu, Yue; Guan, Li; Li, Jiantao; Wang, Yichao; Dong, Guoyi; Tang, Aiwei; Teng, Feng
Highlights: Spin-coating a PEDOT:PSS layer on the ITO to improve the electric properties of EBDs for the first time. The influence of annealing on the electric properties of EBDs is investigated. The current transport mechanism of the different types of devices is discussed in detail. Abstract: Hybrid organic/inorganic electrically bistable devices (EBDs) based on Cu2 S/PVK nanocomposites have been fabricated by using a simple spin-coating method. An obvious electrical bistability is observed in the current-voltage ( I - V ) characteristics of the devices, and the presence of the buffer layer and the annealing process have an important effect on the enhancement of the ON/OFF current ratios. Different electrical conduction mechanisms are responsible for the charge switching of the devices in the presence and absence of the buffer layer.